Focus on nursing pharmacology - Karch, Amy Morrison
Amy Karch has found that students learn best when concepts are built upon each other, growing from simple to complex, building on a foundation of understanding. Organized by body systems, this heavily illustrated book organizes essential nursing pharmacology information into focused, easy-to-learn steps. Building key concepts upon each other, the text gives students a solid foundation of understanding. Easy to understand drug prototype boxes are integrated throughout the book as well as integrated content summaries